Improved Network Integrity and Patient Follow-up After In-Office Needle Arthroscopy Compared to Outpatient Advanced Diagnostic Imaging for Intra-articular Pathology - Elizabeth Ford, D.O; Rachel Frank, M.D; Manuel Pontes, Ph.D; Sean McMillan, D.O (Elsevier, 2024)
Purpose: To evaluate network integrity for diagnostic testing and patient follow-up comparing in-office needle arthroscopy and outpatient advanced diagnostic imaging for intra-articular pathology. Methods: A retrospective chart review was performed to identify patients who were indicated for either in-office needle arthroscopy (IONA) or outpatient advanced diagnostic imaging (OADI). Current Procedural Terminology (CPT) codes 29870 and 29805 with place of service modifier 11 were used to identify patients who underwent IONA of the knee and shoulder, respectively, between January 2020 and March 2023. CPT codes 73721-3 and 73221-3 were utilized to identify patients indicated for outpatient advanced magnetic resonance imaging of the knee or shoulder. All patients who were indicated for the procedure and denied by the insurance were identified and recorded. Inclusion criteria consisted of patients older than 18 years with suspected intra-articular pathology who had failed conservative treatment. Exclusion criteria included patients younger than 18 years, non-English speaking, or those who failed to follow up due to death. The location of where the imaging was performed was recorded (within the health system vs an unaffiliated center). Additionally, patient follow-up with the provider after the diagnostic testing was indicated was recorded. Results: Two separate groups of 100 consecutive patients who were indicated for IONA or OADI were identified and retrospectively chart reviewed. Ninety-four percent of the IONA patients underwent the procedure after it was indicated within the physician office. Sixty-eight percent underwent the procedure the day they were indicated for the procedure. All 94 patients were deemed to have a follow-up with a definitive plan of care after the procedure. Eighty-seven percent of the OADI patients completed their ordered testing. Sixty-two percent (54/87) of the patients had the study performed at one of the primary hospital-affiliated imaging centers. Thirty-eight percent of the studies (33/87) were deemed to have leaked from the system. Of the 87 patients who had the imaging performed, 79% (69/87) had a definitive treatment plan rendered with the lead author (S.M.) based on the imaging results. Twenty-one percent (18/87) of the patients who underwent imaging did not follow up with the treating provider or show for a scheduled follow-up appointment. Nineteen percent (13/69) of the patients who had a definite treatment plan rendered did not come into the office for their results but requested and received them over the phone from the provider. The IONA cohort demonstrated statistically significant (P < .001) network integrity in terms of location of service remaining within the system compared to the OADI group. Furthermore, patient follow-up for definitive treatment plans after IONA was also higher (P < .001) than in the OADI group. Conclusions: IONA results in greater network integrity and patient follow-up compared to conventional imaging. Clinical Relevance: In-office needle arthroscopy performed for the diagnosis of intra-articular pathology may offer a valuable clinical diagnostic tool while providing a meaningful avenue for network integrity and patient retention.